Measuring Diverging House Prices - Jan Rouwendal; Mark van Duijn (Tinbergen Institute, 2017)
House price indexes summarize the development of all house prices in a single number, while actual price movements often differ among market segments. We develop a methodology for measuring house prices as a flexible function of housing services – a one-dimensional quality measure – and apply it to test for the common assumption of identical price movements in all parts of the housing market. Our approach is based on a generalization of the familiar (constant unit price) Muth model to a situation of in which the unit price of housing services may depend on the quality level. We apply the method to a rich set of transaction data referring to Amsterdam in the period 1985-2013. We estimate an indicator of housing services based only on the ranking of house prices in postcode areas during periods of three months and compare the results to conventional hedonic price equations that embody the assumption of a unit price for housing services that does not depend on quality. We develop a test for a constant price per unit of housing services and reject it on the basis of price differences occurring over time as well as over space.
Keywords: R31; R21; D40; 330; housing price; housing quality; Muth model; affordability